Evaluation of a Security Control Lane with the Application of Fuzzy Logic. (2017) - Kierzkowski, Artur; Kisiel, Tomasz
Abstract: The article presents a model for the evaluation of a security control lane at an airport with the application of fuzzy logic. The model allows for carrying out a multi-criteria evaluation of a security control system by considering its capacity, efficiency of prohibited item detection and level of service. The approach presented is complementary to the existing scientific considerations, which, however, have been analysing the system by taking into consideration only one of the aforementioned criteria. Theoretical membership functions were adopted on the basis of which the authors show the advantages of the model developed, the possibility of determining functional relationships between specific input variables and their influence on a security control lane evaluation. The approach proposed allows for selecting an optimal structure of a security control lane and an optimal structure of the security control process.